FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA FAKULTAS BISNIS DAN EKONOMIKA UNIVERSITAS SURABAYA - Tifani Geovana Suyono; Eko Nugroho; Noviaty Kresna Darmasetiawan (Perpustakaan Universitas Surabaya, 2018)
This study aims to examine the factors that affect entrepreneurial intention of students such as educational factor, relationship factor and self confidence factor from students of Faculty of Business and Economics, University of Surabaya.This study uses the quantitative approach by distributing questionnaires to 150 respondents. Software used to analyze data is SPSS 18 for Windows and IBM Amos 22 for Windows. Sample in this research is student of Faculty Business and Economics of University of Surabaya. Dependent Variable in this research is entrepreneurial intention. Independent variables in this study consist of educational support, relationship support and self confidence. The study found that educational support has a positive significant effect on entrepreneurial intention from students of Faculty of Business and Economics University of Surabaya. Relationship support has a positive significant effect on entrepreneurial intention from students of Faculty of Business and Economics University of Surabaya. Self confidence has a positive significant effect on entrepreneurial intention from students of Faculty of Business and Economics University of Surabaya.